2022
DOI: 10.3390/nano12071188
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Etching Process for Graphitic Carbon Nitride Photocatalysts Containing Platinum Cocatalyst: Effects of Water Hydrolysis on Photocatalytic Properties and Hydrogen Evolution Behaviors

Abstract: In this study, we synthesized Pt/g-C3N4 photocatalysts modified by a solvent etching process where ethanol (Pt/CN0), water (Pt/CN100), and a 50:50 mixture (Pt/CN50) were used as a solvent, and investigated the optimal properties of g-C3N4 to prepare the best Pt/g-C3N4 for photocatalytic hydrogen evolution. From diverse characterizations, water was proven to be a stronger solvent agent, resulting in not only the introduction of more O-functional groups onto the g-C3N4 surface, but also the degradation of a regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Moreover, uniform mesoporous structure in these samples was verified by the isotherms under the relative pressure between 0.1 and 0.9. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, uniform mesoporous structure in these samples was verified by the isotherms under the relative pressure between 0.1 and 0.9. [ 43 ]…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, uniform mesoporous structure in these samples was verified by the isotherms under the relative pressure between 0.1 and 0.9. [43] Figure 7 shows the PL spectra of pristine g-C 3 N 4 , the g-C 3 N 4 @Ag composite, and RACN. The emission peak of g-C 3 N 4 at ≈550 nm was greatly quenched in intensity after introduction of Ag nanoparticles, which indicated that the Ag nanoparticles inhibited the recombination of photogenerated electrons and holes of g-C 3 N 4 .…”
Section: Structural Characterizationmentioning
confidence: 99%
“…In addition, various existing researches have proven that implanting the anion–cation into the g-C 3 N 4 frameworks could regulate their bandgap structure for broader visible-light absorption, facilitate the bulk phase and interface charge separation and lead to enhanced photocatalytic activity for H 2 evolution [ 21 , 22 , 23 ]. For instance, Qiao et al [ 24 ] found that a new intermediate energy level was formed in the bandgap of g-C 3 N 4 via the insertion of P into its skeleton, which received the electrons generated by light excitation from VB and thus improved the separation of photocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…The well-known metal-free semiconductor graphitic carbon nitride (g-C 3 N 4 ) has been demonstrated as a promising material for photocatalysis due to its suitable band gap (2.7 eV) for visible light, high physicochemical stability, and ecological friendliness. Nevertheless, the photocatalytic ability of g-C 3 N 4 is restricted in terms of the high recombination of charge carriers, low specific surface area, and inadequate usage of visible light [ 13 , 14 ]. To overcome these issues, numerous attempts have been made to facilitate the photocatalytic behavior of g-C 3 N 4 via heterostructure construction, defects engineering, and doping technology [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the enhancement of the overall performance of materials, the hydrothermal process has been introduced as an effective and uncomplicated method to significantly improve the photocatalytic properties of the g-C 3 N 4 photocatalyst. This facile and green method can etch numerous defects on the g-C 3 N 4 surface and introduce desirable O-containing functional groups to improve photodegradation efficiency [ 13 , 18 ]. However, it was reported that strong hydrolysis in the method also degraded a regular array of tri-s-triazine (melem) units in the g-C 3 N 4 structure [ 17 ].…”
Section: Introductionmentioning
confidence: 99%